(2n-5)(n+1)=0

Simple and best practice solution for (2n-5)(n+1)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2n-5)(n+1)=0 equation:


Simplifying
(2n + -5)(n + 1) = 0

Reorder the terms:
(-5 + 2n)(n + 1) = 0

Reorder the terms:
(-5 + 2n)(1 + n) = 0

Multiply (-5 + 2n) * (1 + n)
(-5(1 + n) + 2n * (1 + n)) = 0
((1 * -5 + n * -5) + 2n * (1 + n)) = 0
((-5 + -5n) + 2n * (1 + n)) = 0
(-5 + -5n + (1 * 2n + n * 2n)) = 0
(-5 + -5n + (2n + 2n2)) = 0

Combine like terms: -5n + 2n = -3n
(-5 + -3n + 2n2) = 0

Solving
-5 + -3n + 2n2 = 0

Solving for variable 'n'.

Factor a trinomial.
(-1 + -1n)(5 + -2n) = 0

Subproblem 1

Set the factor '(-1 + -1n)' equal to zero and attempt to solve: Simplifying -1 + -1n = 0 Solving -1 + -1n = 0 Move all terms containing n to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -1n = 0 + 1 Combine like terms: -1 + 1 = 0 0 + -1n = 0 + 1 -1n = 0 + 1 Combine like terms: 0 + 1 = 1 -1n = 1 Divide each side by '-1'. n = -1 Simplifying n = -1

Subproblem 2

Set the factor '(5 + -2n)' equal to zero and attempt to solve: Simplifying 5 + -2n = 0 Solving 5 + -2n = 0 Move all terms containing n to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -2n = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -2n = 0 + -5 -2n = 0 + -5 Combine like terms: 0 + -5 = -5 -2n = -5 Divide each side by '-2'. n = 2.5 Simplifying n = 2.5

Solution

n = {-1, 2.5}

See similar equations:

| -12+l=-38 | | 3(y-4)-6=-4(-6v+6)-6v | | 2v^2=5v | | -3k+2k+5k+9=-7 | | 2/5m=7/10m=2/7/1/4 | | 2x+4/4=x-8/3 | | z^(2/3)-2z^(1/3)=15 | | fx=5x-1 | | -2y+3w=10 | | 24/y=8/3 | | 4x+5+2x+8= | | 4x-2y-3x+5y= | | 7x^2+20x-18=0 | | 2x+6(-2.5x+5)=-4 | | (-2)x(-25)= | | x+x*x=16 | | -46=3x+7y | | x/9-5/6=4x/9 | | (X-17.7)+19.6=28.8 | | 3-2a=15 | | 7(10x+8)=-364 | | 4y+4-3y=2y-6 | | f(x)=4x^2+6x+3 | | r/3-3/8/r=-3/4 | | 6y+2(3x+5)+2y+3= | | 5(x-3)=4x-9+3x | | 5a+b=2 | | (5.6*10^-6)/(7*10^3)= | | -7x-4(5x-2)=197 | | 3x-3(x+1)=e | | 5.6*10^-6/7*10^3= | | 14x-17=6x-10 |

Equations solver categories